Uk and united-states visitor expenditure in ireland - some econometric findings - Ohagan, Jw; Harrison, Mj (Economic & Social Studies, 1984)
Abstract: This paper analyses trends in the Irish shares of UK and US visitor expenditures in Europe over the period 1964 to 1981. This is done in the context of two larger studies by the authors, the theoretical framework of which is the Almost Ideal Demand System of Deaton and Muellbauer (1980b). Estimates of price and expenditure elasticities of demand for UK and US visits to Ireland are provided.
Keywords: Economics; Sociology